"To work, or not to work, that is the question" – Recent trends and avenues for research on presenteeism. Issue 3 (3rd May 2020) - Ruhle, S. A.; Breitsohl, H.; Aboagye, E.; Baba, V.; Biron, C.; Correia Leal, C.; Dietz, C.; Ferreira, A. I.; Gerich, J.; Johns, G.; Karanika-Murray, M.; Lohaus, D.; et al.
ABSTRACT: This position paper brings together recent and emerging developments in the field of presenteeism. A critical synthesis of the evidence is needed due to persisting conceptual and methodological challenges as well as the increased volume of research in the field. This paper integrates emerging evidence and critical thinking into three areas: (1) concept, (2) measurement and methodological issues, and (3) the context of presenteeism. First, due to the variety of existing definitions, competing understandings, as well as the notion of positive presenteeism, it is important to reconsider the notion of presenteeism. Second, it is important to reflect on the measurement of the act of presenteeism and the productivity loss associated with that. Third, following the call to investigate presenteeism in specific contexts, it is important to explain the social, occupational, cross-cultural aspects, as well as the contemporary workplace changes. Based on this critical synthesis, we conclude by identifying recommendations for future research on presenteeism.